Implementation of Muhammadiyah Islamic Economic Thought in University Economic Governance: A Multiple Case Study at UMY and Unismuh Makassar - Mas'udi, Mohammad; Azhari, Susiknan; Mahmadah Hanafi, Syafiq (Universitas Muhammadiyah Yogyakarta, 2025)
This research aims to understand how Muhammadiyah's Islamic economic thought is implemented in economic management at Muhammadiyah universities, specifically at Universitas Muhammadiyah Yogyakarta (UMY) and Universitas Muhammadiyah Makassar (Unismuh). This study is motivated by Muhammadiyah's commitment to building an economic system that is just and based on Islamic values, as well as the important role of universities as centers for the development of Islamic economic thought and practice. Using a qualitative multi‑case study design, data were collected through in‑depth interviews with 12 informants, consisting of university leaders, directors of business units, lecturers, and Muhammadiyah council representatives. Data analysis followed an inductive thematic approach supported by coding, categorization, and cross‑case comparison, while validity was ensured through triangulation of sources and member checking. The research findings conclude that the implementation of Muhammadiyah's Islamic economic thought in both universities is reflected in three main aspects: (1) institutional policies oriented toward the values of justice and economic independence, (2) integration of Islamic economic values into the curriculum and academic activities, and (3) development of campus-based Islamic business units as a form of equitable economic practice. Despite differences in local context, both universities show similarities in the spirit of Muhammadiyah economic da'wah, which emphasizes ethics, justice, and social welfare. This research contributes to enriching the discourse on the application of Muhammadiyah Islamic economic thought in Islamic higher education and provides recommendations for strengthening the institutionalization of Islamic economics in Muhammadiyah universities in Indonesia.